A New Vector-Based Hysteresis Current Control Scheme for Three-Phase PWM Voltage-Source Inverters - Mohseni, Mansour; Islam, Syed (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2010)
This paper presents a new vector-based hysteresis current controller (HCC) for three-phase pulsewidth modulation (PWM) voltage-source inverters (VSI). The HCC is intrinsically robust to the load parameters variations, exhibits very fast transient performance, and is suitable for simple implementations. Despite these advantages, the conventional HCC has a major drawback when applied to the three-phase PWM-VSI: interphases dependency leads to very high-switching frequencies in the inverter. This paper starts with a review on the vector-based HCCs reported in the literature to address this problem. Then, a new vector-based method is proposed using multilevel hysteresis comparators integrated with a switching table. The proposed method works with the inverter current vector represented in the stationary α- β frame and produces a coordinated switching pattern. The current error is kept inside a square tolerance region without significant increase in the complexity of the hardware implementation. Simulation results show that the proposed vector-based method can retain the advantages of the conventional HCC. However, the steady-state performance of the proposed current regulator is significantly improved by reducing the switching frequency and minimizing oscillations of the inverter current vector. The proposed current controller is finally compared with other reported vector-based methods and its advantages are illustrated.